OBTAINING AND MODELING NANO-SCALE STRUCTURES IN SEMICONDUCTORS - Eshboltayev Iqbol Mamirjonovich,; G‘ofurov Saidkamol Zokirjon ogli,; Eshboltayev Ikromjon Iqbol ogli, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This  paper  presents  a  scientific  analysis  of  methods  for  obtaining  nano-scale structures  in  semiconductors,  as  well  as  issues  related  to  modeling  their  physical properties. The influence of nano-scale effects, quantum confinement phenomena, and surface effects on the properties of semiconductor materials is examined. In addition, prospects  for  designing  nano-scale  structures  based  on  modern  experimental  and theoretical approaches are highlighted.